Circulating Asprosin Concentrations in Patients with Obesity and Carbohydrate Disturbances - Nedeva, Iveta Slavyanova; Assyov, Yavor; Karamfilova, Vera; Vodenicharov, Vlayko; Gerganova, Antonina; Hristova, Julieta; Kamenov, Zdravko (Hormone and Metabolic Research, 2023)
Asprosin is a fasting-induced glucogenic hormone, secreted by white adipose tissue in response to starvation. The aim of the current study was to determine the levels of asprosin in subjects from the entire spectrum of the carbohydrate metabolism. A total of 153 Causcasian subjects participated in this study: group 1, healthy volunteers; group 2, obese subjects without glycemic disturbances; group 3, subjects with prediabetes and group 4, patients with newly identified type 2 diabetes. Subject with body mass index≥30 kg/m2 and dysglycemia (prediabetes and diabetes) showed significantly high levels of asprosin (1.40 ng/ml [IQR=0.98–1.94]; 1.27 ng/ml [IQR=0.86–2.12]; 1.09 ng/ml [IQR=0.89–1.58]) compared to the control group (0.71 ng/ml [IQR=0.54–0.92]; p<0.001). Correlation analysis showed that serum asprosin also had significant positive associations with some anthropometric parameters, liver enzymes, fasting and post load glucose and insulin, LDL and triglycerides. Furthermore, we estimated a marked relationship between asprosin concentrations and intima media thickness of the common carotid artery as well as neuropathy disability and vibration sensitivity. The circulating asprosin levels for differentiating subjects with carbohydrate disturbances and those with obesity were determined by ROC analysis. The AUC for disturbances of the glucose metabolism was 0.672 (p<0.001; 95% CI=0.581–0.751) and for obesity AUC was 0.849 (p<0.001; 95% CI=0.785–0.919). Circulating asprosin could be used as a predictive factor for early carbohydrate disorders and might be a potential new therapeutic target for the treatment of dysglycemia and obesity. Further prospective studies are needed to confirm this observation.
Keywords: obesity; metabolic syndrome; prediabetes; asprosin; adipokines